Pengaruh Budaya Organisasi, Kedisiplinan, dan Kompetensi Terhadap Kinerja Pengawasan - Saraswati, Komang Sukma; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2019)
This research was conducted at the Regional Inspectorate and the Regional Financial and Revenue Management Agency of Klungkung Regency. The number of samples taken as many as 42 employees, with non-probability sampling method, proposive sampling technique. Data collection is done through surveys and questionnaires. The analysis technique used is multiple linear regression. Based on the results of the analysis it was found that organizational culture, discipline, and competence simultaneously had a significant effect on supervisory performance. This shows that the implementation of a good organizational culture, the application of discipline and the establishment of competency standards for employees, the performance of supervision will improve. Partially organizational culture, discipline, and competence also influence supervisory performance. This shows that with the implementation of a good organizational culture, discipline and competence can improve supervisory performance. Keywords: Organizational culture, discipline, competence